Universiti Tun Hussein Onn Malaysia Bike Rental System - Azizan, Nor Aisyah Najwa; Omar, Nurul Aswa (Applied Information Technology And Computer Science, 2024)
Bike rental service is a business operation that rents bicycles for certain amount of time. With the modernization of services throughout modern civilization, the bike rental service is upgraded from manual filing to computerized system. Due to this, Universiti Tun Hussein Onn Malaysia (UTHM) Bike Rental System had been proposed mainly for students and staff to know the availability of the bike rental. The project’s objective is to design the third-party lease which is ‘The Right Bike Store’ a bike rental system that caters to the bike rental services provided in the UTHM by developing mobile application for users and web application for the staff and administrators. This system limits to UTHM staff and students only. The methodology chosen to develop UTHM Bike Rental System is Waterfall model. By using the methodology of the Waterfall model, the tasks distribution is divided into planning, analysis, design, implementation and testing stages. The software used to develop this system which are the Visual Studio Code for the web application by using Hypertext Markup Language (HTML), Cascading Style Sheets (CSS), JavaScript and Hypertext Preprocessor (PHP). The mobile application is developed by using Android Studio and the language of Java and Extensible Markup Language (XML). This system consists of eight modules and uses five main keys to store data in Firebase real-time database. The mobile application of this system caters only to the users which are the students and staff of UTHM while the web application caters only to the employees which consists of administrators and staff.